Thee cases of the plasmocytoma localised in the facial sceleton - Lewandowski, Bogumił; Pakla, Paweł (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This article presents pathogenesis, division, clinical features, diagnostic criteria, treatment and prognosis of different myeloma`s entities. The authors report and compare with data from literature three different myeloma`s cases of the face bones and oral cavity which were treated for this neoplasm in the Ward of Maxillofacial Surgery of District Specialised Hospital in Rzeszow. Attention was paid to the symptoms of the disease when it effects the jaws and oral cavity. We also emphasise differential diagnostic problems.